TREATMENT OF ENDOMETRIOID OVARIAN CYSTS CONCERNING FERTILITY: A REVIEW OF MODERN METHODS - Борис Исаевич Айзикович; Семен Вадимович Зотов; Виталий Михайлович Кулешов; Полина Юрьевна Мотырева; Сергей Николаевич Филимонов; Виктория Васильевна Лихачева (The Publishing House Medicine and Enlightenment, 2021)
To date, the question of choosing the optimal treatment for endometrioid cysts in infertile women remains relevant. The ovarian reserve of such women is influenced by both the endometrioma itself and the surgery to remove it. This paper provides an analysis of the literature and an overview of modern approaches to the treatment of endometrioid ovarian cysts concerning preserving or restoring fertility. The endometrioma influence on the ovarian anatomy and physiology is considered. The comparison of the surgical approach with minimally invasive techniques: aspiration, sclerotherapy of endometrioid cysts is provided. Attention is paid to the effectiveness of assisted reproductive technology in patients after the endometrioma treatment by different methods.